Do poder pastoral ao cuidado de si: a governabilidade na enfermagem - Lunardi, Valeria Lerch (1997)
In her thesis, founded on Foucault, the author intends to ofter answers to how nursing governs itself, lets itself be governed and govern others, bringing a specific focus to bear on the frontiers between the one’s own care, as a technology of the self which is proper of the Greek thought and the “pouvoir pastoral”. The methodologic roas has followed two parallel axes of analysis where a cartography of power relationships is developed. Comprehension is sought of the strategies and struggles whereby knowledge, subjects and practices have been built, and also by designing techniques which enlarge those autonomy spaces pertaining to the client and to nursing, in pursuing an ethic enterprising seen as the action resulting from autonomous decision and will. That cartography has been performed along two differentiated routes focusing the rupture of the religious model with Nightingale and of the religious thought in the production of the “Revista Brasileira de Enfermagem” (Brazilian Nursing Journal) from to 1980 to 1995. By discourses analysis, demonstration is thus offered that, where ruptures are pointed, the survival is seen of these strategies of power identified by Foucault as “pouvoir pastoral”. The perspective of this analysis of power presents as the government of others, of which one of the focuses is the health of people as a responsability of nursing, and where the client is apparently destined to occupy the place of object of care. The ethic analysis perspective has an approach to care of oneself as an ethic concern, and self-care is thought of as care of oneself and as the objective of nursing assistance. This allows the client to exercise autonomy both as the subject and as the end to health. Through nursing practices, the study identifies the responsability, the obedience, confession and mortification of the self characterized as the elements which are proper of “pouvoir pastoral; also, the technologies of one’s own care are made evident, as well as the possibilities to introduce changes in the manner ofbeing and doing nursing.